Nuevas funciones y mecanismos de acción del factor neurotrófico derivado de células gliales, GDNF; en el desarrollo del sistema nervioso - Irala, Dolores (2016)
GDNF and its co-receptor, GFRa1, play a key role in synaptic maturation during\nnervous system development through ligand-induced cell adhesion molecule mechanism.\nThe aim of this project was to study the role of GDNF and GFRa1 in postsynaptic\nmaturation and development of hippocampal neuronal circuits. We have shown that\nGDNF/GFRa1 complex regulates dendritic growth and complexity of pyramidal neurons\nboth in vitro and in vivo. Furthermore they promote dendritic spine formation and\npostsynaptic maturation recruiting excitatory postsynaptic proteins such as Homer1 and\nNMDAR1 to the postsynaptic density. GFRa1 deficient mice show a reduction in synapse\ndensity and in different synaptic parameters in vivo regarding wild type mice. Finally, we\nhave identified NCAM-180 as the mediator of the intracellular signaling of GDNF/GFRa1\ncomplex in the postsynaptic membrane, since in the absence of this protein postsynaptic\neffects induced by GDNF and GFRa1 are lost.\nIn this thesis we have identified GDNF, GFRa1 and NCAM-180 as a molecular\ncomplex required for neural circuits development, through the regulation of dendritic tree\ngrowth, synapse formation and postsynaptic maturation.